Ginkgo biloba exocarp extracts inhibit S. aureus and MRSA by disrupting biofilms and affecting gene expression. (10th May 2021) - Wang, Bing; Wei, Peng-Wei; Wan, Shan; Yao, Yang; Song, Chao-Rong; Song, Ping-Ping; Xu, Guo-Bo; Hu, Zu-Quan; Zeng, Zhu; Wang, Cong; Liu, Hong-Mei
Abstract: Ethnopharmacological relevance: Ginkgo biloba L. fruit, also known as Bai Guo, Ya Jiao Zi (in pinyin Chinese), and ginkgo nut (in English), has been used for many years as an important material in Chinese traditional medicine to treat coughs and asthma and as a disinfectant, as described in the Compendium of Materia Medica (Ben Cao Gang Mu, pinyin in Chinese), an old herbal book. Ginkgo nuts are used to treat phlegm-associated asthma, astringent gasp, frequent urination, gonorrhoea and turgidity; consumed raw to reduce phlegm and treat hangovers; and used as a disinfectant and insecticide. A similar record was also found in Sheng Nong's herbal classic (Shen Nong Ben Cao Jing, pinyin in Chinese). Recent research has shown that Ginkgo biloba L. exocarp extract (GBEE) can unblock blood vessels and improve brain function and exhibits antitumour and antibacterial activities. Aim of study: To investigate the inhibitory effect of Ginkgo biloba L. exocarp extract (GBEE) on methicillin-resistant S. aureus (MRSA) biofilms and assess its associated molecular mechanism. Materials and methods: The antibacterial effects of GBEE on S. aureus and MRSA were determined using the broth microdilution method. The growth curves of bacteria treated with or without GBEE were generated by measuring the CFU (colony forming unit) of cultures at different time points. The effects of GBEE on bacterial biofilm formation and mature biofilm disruption were determined by crystal violet staining. Quantitative polymerase chain reaction (qPCR) was used to measure the effects of GBEE on the gene expression profiles of MRSA biofilm-related factors at 6, 8, 12, 16 and 24 h. Results: The minimum inhibitory concentration (MIC) of GBEE on S. aureus and MRSA was 4 μg/mL, and the minimum bactericidal concentration (MBC) was 8 μg/ml. Moreover, GBEE (4–12 μg/mL) inhibited S. aureus and MRSA biofilm formation in a dose-dependent manner. Interestingly, GBEE also destroyed mature biofilms of S. aureus and MRSA at 12 μg/ml. The expression of the MRSA biofilm-associated factor icaA and sarA were downregulated after 6 h of treatment with GBEE, while sigB was downregulated after 12 h. MeanwhileMeanwhile, icaR was upregulated at 12 h. In addition, GBEE also downregulated the virulence gene hld and inhibited the synthesis of staphyloxanthin. Conclusions: GBEE has excellent antibacterial effects against S. aureus and MRSA and inhibits their biofilm-forming ability by altering related gene expression. Graphical abstract: Image 1